STRATEGI KOOPERATIF DAN KEUNGGULAN KOMPETITIF - Laoh, Sinjo James (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
Firm’s critical resources may span firm boundaries and may be embedded in interim. Resource and routines increasing important unit of analysis for understanding competitive advantages is the relationship between firms and identify four potential sources of inter organizational competitive advantage such as:  relations specific assets, knowledge sharing, complementary resources and capabilities, and effective governance. Corporate revenue in turn could be attained through interrelation of the industrial characteristic structure towards its bargaining power, barriers to entry and substitute of product or services.